Ratiometric Sensing and Discrimination of Rutile and Anatase TiO2 Nanoparticles by a Quinoline-Benzimidazole Conjugate - Suguna, S.; Velmurugan, K.; Sheebha, I.; Immanuel David, C.; Vidhya, B.; Prabhu, J.; Nandhakumar, R. (Asian Journal of Chemistry, 2021)
A quinoline-benzimidazole conjugate 1 has been synthesized as a potential probe to discriminate the TiO2 anatase and rutile nanoparticles by fluorimetry. Probe 1 exhibits selective TiO2 sensing through a photoinduced electron transfer process (PET) and the ratiometric sensing response by intramolecular charge transfer (ICT) mechanism. The binding ratio and the association constants were also calculated. The limit of detection of TiO2 nanoparticles by probe 1 was upto micro molar concentrations.